Sensitivity and specificity of a quantitative point of care D-dimer assay using heparinized whole blood, in patients with clinically suspected deep vein thrombosis - Dempfle, Carl-Erik; Korte, Wolfgang; Schwab, Michael; Zerback, Rainer; Huisman, Menno V.; on behalf of the CARDIM study group (Thrombosis and Haemostasis, 2006)
D-dimer assays are efficient in the exclusion diagnostics of deep vein thrombosis (DVT) in patients without severe concomitant diseases. We have determined diagnostic sensitivity and specificity of a new point-of-care rapid assay for quantitative determination of D-dimer in heparinized whole blood in outpatients with suspected DVT. In 19 participating centers, 637 patients were included in the study, of which 77 were excluded, the majority because of inadequate documentation of analytical quality control measures. DVT was diagnosed in 223 of the remaining 560 patients by duplex ultrasound examination. The POC D-dimer assay showed a high sensitivity of 96.9% for the diagnosis of DVT and a high specificity of 60.8% at a pre-specified cutoff of 0.5 µg/ml. For Tina-quant D-dimer, sensitivity was slightly lower at 94.9%, with a specificity of 64.8%.The VIDAS D-dimer assay showed a sensitivity of 98.2%, but specificity was 40.7%. The area under the curve (AUC ± standard error, 95% confidence interval) was 0.879 ± 0.019 (0.845–0.909) for POC D-dimer, 0.908 ± 0.016 (0.877–0.934) for Tina-quant D-dimer, and 0.895± 0.018 (0.862–0.922) forVIDAS D-dimer. Differences were not statistically significant. The new whole blood POC D-dimer assay isa reliable tool for exclusion of DVT in symptomatic outpatients, displaying a comparable diagnostic performance as VIDAS D-dimer and Tina-quant D-dimer assays.Roche CARDIAC and TINA-QUANT are tradenames of Roche.
Keywords: Deep vein thrombosis; D-dimer; point-of-care assay